PENGARUH GOOD GOVERNANCE TERHADAP KUALITAS LAPORAN KEUANGANKDENGAN SISTEM PENGENDALIAN INTERNAL SEBAGAI PEMODERASI (Studi Kasus Pada Aparatur Organisasi Perangkat Daerah Kab. Karanganyar) - Amanda Thea Hosana; Rispantyo Rispantyo; Bambang Widarno (Universitas Slamet Riyadi, 2020)
This study was conducted to determine the effect of good governance onthe quality of local government financial reports, the effect of internal controlsystems on>the quality of local government financial reports, the internalcontrol system moderates the effect of good governance on the quality of localgovernment financial reports. This study uses primary data from the answersto the questionnaires distributed to officials of the Karanganyar RegencyRegional Government Organization. The sampling technique was taken usingpurposive sampling method, amounting to 72 respondents. The data analysistechnique used in this research is descriptive statistical test, validity test,reliability test, classical assumption test, multiple linear regression analysistest, t test, F test, determination test (R2) and MRA absolute difference test.The result of the research states that good governance and internal controlsystems have a significant positive effect. The result of moderation regressionanalysis with absolute difference value test shows that the internal controlsystem isn’t able to negatively moderate the relationship of good governance tothe quality of local government financial reports.